Child-Rearing Practices and Temperament of Children: Are They Really Determinants of Children's Aggression? - Supra Wimbarti (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 1997)
Very few studies on children's aggression conducted in the Easternculture, even though studies on children's aggression in the Westernculture are numerous. This study attempted to examine the roles ofvarious childrearing practices and temperament of children in contributÂing to children's aggression in Javanese culture. Fifty-eight preschool children and their mothers participated in this study. Data were colÂ lected by means of school and home observation, and interview withthe mothers. Level of maternal education, nurturant of the mothers,and several types of temperament of the children significantly predictedchildren's aggression.Key Words: Child-rearing practice, temperament of children, children's aggression